Drying Characteristics of Jelly Ear Mushroom (Auricularia auricula) Using Microwave Oven - Ning Puji Lestari; Dian Purbasari; Mochamad Sholihuddin; Iwan Taruna (The University of Lampung, 2023)
Jelly ear mushroom (Auricularia auricula) is easily damaged due to high water content of around 85-95%. Therefore, it is necessary to dry it to extend the its shelf life. The purpose of this study was to determine the drying characteristics and physical properties of jelly ear fungus from microwave drying. The treatment combined of blanching consisted of three levels (non-blanching, blanching 2 min, and blanching 5 min) and microwave power (422 W, 579 W, and 782 W). The research was designed randomly with 3 replications. The results showed that blanching treatments and microwave power could reduce the water content from the range of 86,23-88,39% (wet basis) to 6,65-7,89 % without blanching, 6,91-7,92 % with 2-min blanching, and 6,63-8,54 % with 5-min blanching treatment. The drying rate increased with microwave power. Treatment of non-blanching with wicrowave power of 782 W resulted in the largest color change (∆E), mamely 74.156, while 2-minute blanching with power of 422 W caused the lowest color change of 43,214. The highest rehydration ratio occurred in the 2-minute blanching treatment, but the rehydration ratio for non-blanching and 2-min blanching treatments tended to decrease as the microwave power increased.Keywords: Mushroom, Microwave, Drying rate, Fehydration ratio, Color change